The Mechanisms for Employing Artificial Intelligence in Saudi Journalisms and its Impact on the Development of Journalistic Content - Almania, Ali Mohammed (Journal of Ecohumanism, 2024)
This study examined the mechanisms of employing artificial intelligence in the Saudi press and its implications for the development of journalistic content. It aims to identify the extent to which artificial intelligence techniques are employed in the Saudi press, the most prominent techniques used, measure the extent of journalistic leaders’ awareness of the role of artificial intelligence techniques in the development of journalistic content, and reveal the most important Challenges facing the use of artificial intelligence techniques in Saudi journalism, and how to overcome them. The importance of the study is highlighted by the fact that it examines the extent to which Saudi newspapers keep up with modern technologies to develop their journalistic content, and the extent of clarity of vision among Saudi press leaders regarding artificial intelligence technologies, and their importance in media transformation, especially in light of the technical challenges and rapid developments in the media industry. The researcher relied on the survey method to monitor the opinions of journalistic and technical leaders in the newspapers of the study sample through in-depth, unstructured interviews, to obtain deeper knowledge about the variables of the study. The study concluded that the use of artificial intelligence techniques in the Saudi press is very limited, and thus its weak reflection on the development of journalistic content. The results of the study revealed that there is a disparity in the level of awareness and knowledge of the role of artificial intelligence techniques in journalistic work, among editors-in-chief on the one hand, and between editors-in-chief and technology managers on the other hand, in addition to the lack of a clear vision and future strategies for Saudi press institutions in benefiting from artificial intelligence, which created a gap between the content presented in these newspapers and what the public is looking for. Moreover, the results of the study also showed that there are many challenges facing the use of artificial intelligence techniques in the Saudi press, the traditional way in which Saudi newspapers operate the inefficiency of applications in supporting the Arabic language, and the danger of fake information.